Impact of Extending Beta-Lactam Infusions on IV Access Requirements - Kirstin J. Kooda, PharmD; Julia Nelson, BS; Sara E. Ausman, PharmD; Christina G. Rivera, PharmD; Omar M. Abu Saleh, MBBS; Andrew D. Rule, MD; Ryan W. Stevens, PharmD; Micaela N. Warfield, PharmD; Yanjun Zhao, PharmD; Erin F. Barreto, PharmD, PhD; on behalf of the Beta Lactam Optimization and Outcomes Management (BLOOM) Study Group; Laura M. Dinnes, PharmD; et al. (Critical Care Explorations)
This study aimed to determine if extended infusion (EI; over > 3 hr) beta-lactam therapy increased IV access requirements compared with traditional dosing (TD; over 30 min). Eighty-six adult ICU patients treated with TD anti-pseudomonal beta-lactams who underwent therapeutic drug monitoring (TDM) were included. Patients who transitioned from TD to EI after TDM (EI group) were matched 1:1 to patients who remained on TD. In the primary analysis, the median (interquartile range) total number of lumens in the 24 hours before TDM compared with the 48 hours after TDM were similar between groups (pre: TD 3 [2–5] vs. EI 4 [3–5]; p = 0.22 and post: TD 3 [2–4] vs. EI 4 [3–5]; p = 0.05). Delivery of beta-lactams via EI was not associated with a need for more IV access. Practical challenges such as access should not limit use of EI beta-lactams when indicated.